Single-Nucleus Chromatin Accessibility Landscape Reveals Diversity in Regulatory Regions Across Distinct Adult Rat Cortex - Yu, Yeya; Wei, Xiaoyu; Deng, Qiuting; Lan, Qing; Guo, Yiping; Han, Lei; Yuan, Yue; Fan, Peng; Wu, Peiying; Shangguan, Shuncheng; Liu, Yang; Lai, Yiwei; et al. (Frontiers in Molecular Neuroscience, 2021)
Rats have been widely used as an experimental organism in psychological, pharmacological, and behavioral studies by modeling human diseases such as neurological disorders. It is critical to identify and characterize cell fate determinants and their regulatory mechanisms in single-cell resolutions across rat brain regions. Here, we applied droplet-based single-nucleus assay for transposase-accessible chromatin using sequencing (snATAC-seq) to systematically profile the single-cell chromatin accessibility across four dissected brain areas in adult Sprague–Dawley (SD) rats with a total of 59,023 single nuclei and identified 16 distinct cell types. Interestingly, we found that different cortex regions exhibit diversity in both cellular compositions and gene regulatory regions. Several cell-type-specific transcription factors (TFs), including SPI1, KLF4, KLF6, and NEUROD2, have been shown to play important roles during the pathogenesis of various neurological diseases, such as Alzheimer’s disease (AD), astrocytic gliomas, autism spectrum disorder (ASD), and intellectual disabilities. Therefore, our single-nucleus atlas of rat cortex could serve as an invaluable resource for dissecting the regulatory mechanisms underlying diverse cortex cell fates and further revealing the regulatory networks of neuropathogenesis.